Peran Ayah Terhadap Perkembangan Karakter Anak - Reva Ananda Rudiana; Wahyu Agung Prasetyo; Muhammad Irfani; Alfian Muchammad Zidane (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The aim of this research is to find out how the role of a father influences the character of students at MA Al Islam Jamsaren Surakarta. The respondents of this research were the guidance and counseling teachers at the school. This research method uses qualitative through a case study approach. The data collection technique uses structured interviews, namely preparing questions that require an explanation and then conveying them to the respondent, namely the guidance and counseling teacher. The results of the research show that some students have their character and personality affected by not being able to play the role of a father, which causes some students to want to get attention from other people, either by committing mischief or wanting to pay attention to the opposite sex. This explains that the role of the father is very important in the development of character and 3 aspects (cognitive, affective, psychomotor) of a child and is also able to control the child's behavior while at school.